Targeting scapular muscles with facilitatory movement patterns to improve upper extremity function in gangliocapsular stroke: a case report - Akshaya Saklecha; Moh’d Irshad Quershi; Raghumahanti Raghuveer; Pallavi Harjpal (Journal of Medical Case Reports)
Abstract Background Gangliocapsular stroke is a specific type of hemorrhagic stroke that primarily affects the basal ganglia and internal capsule due to rupture of the lenticulostriate perforating arteries. Patients afflicted with this condition often present with contralateral motor deficits, particularly affecting the upper extremity. Additionally, these individuals may experience challenges in coordination and stability, largely due to the involvement of the shoulder and scapular girdle. The stability of proximal joint is essential to increase the limited functions and distal movement of the upper extremities. Malalignment of scapula further complicates the execution of daily activities, profoundly affecting patients’ overall well-being and reducing engagement in society. Therefore, restoring upper limb function is imperative for a successful return to daily routines, with a focus on improving arm function being a crucial aspect of stroke therapy. Many methods have been explored for enhancing the function of upper limb in stroke, but the emphasis is more toward developing independence in grasp and improving scapular stability is often neglected. This case reports aim to examine the effect of targeted scapular proprioceptive neuromuscular facilitation on upper limb function in a patient who suffered a gangliocapsular stroke. Case presentation A 54-year-old South Asian man was presented with left-sided hemiplegia following a right gangliocapsular stroke. He reported challenges in using his left upper limb and weakness of the left side of the body, which severely impaired his ability to perform activities of daily living. Radiological findings indicated a right gangliocapsular hemorrhage. The patient underwent a 4-week physiotherapy rehabilitation program, with outcome measures including the palpation meter, Fugl–Meyer assessment of upper extremity, and functional independence measure. Following the treatment period, significant improvements were observed in scapular alignment and upper limb functions, underscoring the effectiveness of rehabilitation strategies for optimal outcomes and recovery. Conclusions The study underscores the beneficial outcomes of targeted scapular muscles through facilitatory movement patterns to improve upper extremity function in gangliocapsular stroke. Implementing scapular proprioceptive neuromuscular facilitation techniques led to a beneficial change in scapular positioning, consequently improving upper limb function, and quality of life significantly.